2014
DOI: 10.1371/journal.pone.0105803
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Multilocus Variable Number of Tandem Repeat Analysis (MLVA) for Listeria innocua and Its Application in a Food Processing Plant

Abstract: Listeria innocua is an important hygiene indicator bacterium in food industries because it behaves similar to Listeria monocytogenes, which is pathogenic to humans. PFGE is often used to characterize bacterial strains and to track contamination source. However, because PFGE is an expensive, complicated, time-consuming protocol, and poses difficulty in data sharing, development of a new typing method is necessary. MLVA is a technique that identifies bacterial strains on the basis of the number of tandem repeats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Once L. monocytogenes enters the processing facilities it is unlikely to be eradicated if proper monitoring programmes are not intensive as its survival is influenced by several complex factors (Carpentier & Cerf 2011 ). The contributing factors to survival of L. monocytogenes include the ability to proliferate under harsh stress conditions such as low temperature, pH and osmotic stress (Takahashi et al 2014 ), resistance to sanitation agents and formation of biofilms (Carpentier & Cerf 2011 ). Meat-processing facilities use cold storage (4 °C) to reduce the proliferation of bacteria on meat.…”
Section: Occurrence Of Listeria Monocytogenes In Mmentioning
confidence: 99%
“…Once L. monocytogenes enters the processing facilities it is unlikely to be eradicated if proper monitoring programmes are not intensive as its survival is influenced by several complex factors (Carpentier & Cerf 2011 ). The contributing factors to survival of L. monocytogenes include the ability to proliferate under harsh stress conditions such as low temperature, pH and osmotic stress (Takahashi et al 2014 ), resistance to sanitation agents and formation of biofilms (Carpentier & Cerf 2011 ). Meat-processing facilities use cold storage (4 °C) to reduce the proliferation of bacteria on meat.…”
Section: Occurrence Of Listeria Monocytogenes In Mmentioning
confidence: 99%
“…An assessment of the capacity of MLVA‐CE to identify Listeria innocua , an important hygiene indicator bacterium, revealed that the method detected 60 L. innocua strains, which were classified into 11 patterns. These results indicate that the MLVA‐PCR‐CE approach is an effective method of tracking contamination sources (Takahashi and others ).…”
Section: Procedures For Food Analysis Based On Ce‐based Nucleic Acid Dmentioning
confidence: 68%
“…Multilocus Variable-number Tandem Repeat Analysis (MLVA) is a Polymerase Chain Reaction (PCR) based typing method that characterizes bacteria through the detection of tandem repeats at several specific loci in the genome of bacteria [ 37 ]. This method types bacterial strains by exploiting the fact that the number of repeat units in the variable number of tandem repeats region varies from strain to strain [ 38 ]. Among other typing methods, MLVA is considered a rapid, robust, and convenient bacterial subtyping method with reliable discriminatory power for genotyping bacterial isolates [ 36 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Murphy et al [ 29 ] developed an MLVA protocol for typing L. monocytogenes isolates from salmon and other related food products. Takahashi et al [ 38 ] developed an MLVA protocol for typing L. innocua isolates originating from a food processing facility with the intention of identifying the contamination routes. Miya et al [ 41 ] also used this method to type L. monocytogenes serotype 4b isolates that had been previously characterized by PFGE, EcoRI ribotyping, and MLST and concluded that MLVA highly discriminated the isolates.…”
Section: Introductionmentioning
confidence: 99%